Predictors of mortality in patients receiving exclusive parenteral nutrition: a retrospective cohort study - Flores Palacios, Rodrigo Jesús (2024)
Objective: To identify predictors of mortality in patients receiving exclusive parenteral nutrition due to the inability of the enteral route. Materials and Methods: We conducted a retrospective cohort study of adults who received exclusive parenteral nutrition (EPN) due to enteral route inability from 2019 to 2023 at Hospital III Daniel Alcides Carrión in Tacna, Peru. Predictors of mortality were analyzed using the Cox proportional hazards model. Results: A total of 104 patients were evaluated, 52.9% of whom were men. The most common comorbidities were hypertension (31.7%), cancer (30.8%), and diabetes (21.2%). The median hospital stay duration was 21.5 (IQR 13.5-33.5) days. Multivariate analysis showed that age ≥ 60 years, leukocytes ≥ 12000 cells/mm³, and platelet count < 150x10³ cells/mm³ at the start of EPN were predictors of mortality with adjusted HRs of 8.45 (95% CI: 1.99-35.86), 3.89 (95% CI: 1.45-10.39), and 3.06 (95% CI: 1.46-10.39), respectively. Conclusions: Age ≥60 years, leukocytes ≥12000 cells/mm³, and platelet count <150x10³ cells/mm³ are predictors of mortality in patients receiving exclusive parenteral nutrition.